Lovextortion: Persuasion strategies in romance cybercrime. (June 2020) - Anesa, Patrizia
Highlights: Online romance scams tend to follow recurrent structural patterns. Scam templates are logically structured and organized so that every possibility is contemplated. The excessive use of romantic words and notably clichéd expressions should generate alert. The narrative structure creates an illusion of authenticity. The results are being used to develop an application for the detection of romance scams. Abstract: Online romance scams represent a growing global phenomenon. This study investigates a corpus of authentic messages of this type written in English, focusing on their structural, discursive, and linguistic features. The analysis shows that errors of judgment are exploited by scammers in order to lead victims to an inability to recognize an attempted fraud, despite the signs present in the message. The data obtained may contribute to the development and production of guidelines to be circulated widely, especially on sensitive sites online (e.g. dating sites), to help end-users to become more knowledgeable about adversarial fraudulent strategies.